Development of a DNA microarray platform for the detection of viruses transmitted by small mammals and arthropods - Khan, Mohd Jaseem (2015)
Human activities have being responsible for the global environmental changes, resulting in an increase number of incident of vector- and rodent-borne diseases worldwide. Rodents and arthropods-borne viruses are important globally emerging and re-emerging viruses and most of them are RNA viruses. Efficient and early diagnosis of these infections are very important to prevent their spread, to improve clinical management of the patients, as wells to protect livestock and domestic animals. Currently, available diagnostic methods such as immunoassays, polymerase chain reaction and virus isolation can detect only one or few viruses in a single assay. The DNA microarray platform has emerged as diagnostic tool suitable for high throughput screening of pathogenic agents. The aim of this study was to develop a DNA microarray platform (RoboArboVirusChip) for detecting rodent- and arthropod-borne viruses, which belong to seven families: Bunyaviridae (genera Orthobunyavirus, Nairovirus and Phlebovirus), Flaviviridae (genus Flavivirus), Togaviridae (genus Alphavirus), Reoviridae (genera Orbivirus, Seadornavirus and Coltvivirus), Rhabdoviridae (genera Vesiculovirus and Ephemerovirus), and Asfarviridae (genus Asfarvirus). Specific oligonucleotide probes of 60-mer (n=4209) targeting 412 virus species and generic probes of 25-35-mer (n=87) targeting viruses at the genus level were designed. A total of 17 reference viruses belonging to the Bunyaviridae, Flaviviridae, Rhabdoviridae and Togaviridae families were used to standardize RoboArboVirusChip. All reference viruses were specifically detected without any cross hybridization; however, the generic probes were not able to identify the viruses at the genus level. The RoboArboVirusChip was able to specifically identify four viruses contained in three different mixtures: i) virus of different families, ii) virus of the Flavivirus genus, and iii) the Dengue virus (DENV) serotypes. The four DENV serotypes were use to evaluate the sensitivity of the RoboArboVirusChip, which was able to detect a minimum of 25 RNA copies/mL of the viruses, confirming its high sensitivity. The applicability of the RoboArboVirusChip to detect viruses in clinical samples was tested with serum samples obtained from dengue suspected cases (four positive cases and 40 negative cases). DENV was detected in the four positive serum samples, while in the 40 negative serum samples, it was not detected any virus. The results obtained in this study suggest that the RoboArboVirusChip platform could be a useful tool for early diagnosis of robovirus and arbovirus infections during epidemic outbreaks, helping in the rapid implementation of disease containment strategies